Urolithin A-induced mitophagy: a mitochondrial therapeutic axis for decelerating musculoskeletal aging and modulating knee osteoarthritis pain - Aavrati Rastogi; Roop B. Kalia; Mukesh Bairwa (International Journal Of Community Medicine And Public Health, 2026)
Knee osteoarthritis (OA) is a disease characterized by cellular energy dysregulation, in which structural joint deterioration and chronic pain are caused by mitochondrial dysfunction. OA is now recognized as a multifactorial condition caused by disturbed cellular homeostasis, metabolic imbalance, and typical biological processes of aging, notably mitochondrial dysfunction. However, it was once thought to be caused by mechanical wear and cartilage degradation